The Soybean Industry : With Special Reference to the Competitive Position of the Minnesota Producer and Processor - Goldberg, Ray A. (Book collections on Project MUSE., 1952)
The rapid development of the soybean industry in the United States is reflected in the growth of the industry in Minnesota, a state that now ranks sixth in total production. This state was one of the last to develop a soybean crop, but in the decade from.